"Search less, verify more"—Reviewing salivary biomarkers in oral cancer detection. (5th March 2020) - Adeoye, John; Brennan, Peter A.; Thomson, Peter
Abstract: Oral squamous cell carcinoma is one of the commonest head and neck malignancies with approximately 350 000 cases reported annually and a mortality rate of 50% often attributed to late clinical presentation. Due to the close relationship between saliva bio‐fluid and tumour lesions, optimizing salivary biomarkers for disease detection and screening provides a major new research direction in diagnostic oral oncology. As inter‐tumour heterogeneity and intra‐tumour heterogeneity are common within oral cavity neoplasms, it is unlikely that a single diagnostic or "risk‐stratifying" saliva biomarker will suffice for universal translation to clinical practice. Therefore, this article highlights a number of promising saliva biomarker combinations for oral cavity cancer detection that require further research and validation to determine their true diagnostic potential.